An organic compound having multiple heteroatoms and an organic electroluminescent device containing the same

By introducing organic compounds with a combination of phosphine + phenanthroline structure into nCGL materials, the problems of insufficient thermal stability and electron transport rate of the existing n-type charge generation layer materials are solved, higher electron transport capabilities and device stability are achieved, and the overall performance of OLED devices is improved.

CN119219701BActive Publication Date: 2025-04-18SHIJIAZHUANG CHENGZHI YONGHUA DISPLAY MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411730903.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-04-18
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The existing n-type charge generation layer materials have shortcomings in thermal stability and electron transport rate, resulting in stability and lifetime problems of stacked OLED devices.

Method used

Using organic compounds with multiple heteroatoms, by introducing a combination of phosphine + phenanthroline structures into the nCGL material, high electronegative atoms such as nitrogen, oxygen, and phosphine are used to reduce the maximum negative electrostatic potential of the material, and improve electron transport capability and device stability.

Benefits of technology

The electronic transmission capability of nCGL materials and the voltage and life of the device are significantly improved, the driving voltage is reduced, and the device film stability after doping metal is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219701B_ABST
    Figure CN119219701B_ABST
Patent Text Reader

Abstract

The present invention discloses an organic compound with multiple heteroatoms and an organic electroluminescent device comprising the same. The general structural formula of the organic compound is shown in Formula I, wherein R1-R4 each independently represents hydrogen, deuterium, a substituted or unsubstituted alkyl group with a carbon number of C1-C30, a substituted or unsubstituted aryl group with a carbon number of C6-C60, a substituted or unsubstituted condensed aromatic group with a carbon number of C6-C60, any one of the groups shown in Formula II, and at least two of R1-R4 represent the groups shown in Formula II. The organic compound provided by the present invention introduces phosphine oxygen and phenanthroline structures into the structure, and under the introduction of highly electronegative atoms such as nitrogen, oxygen, and phosphine, has a lower maximum negative electrostatic potential, which is beneficial to improving the stability and electron transmission ability of nCGL materials, thereby effectively reducing the driving voltage of the prepared organic electroluminescent device, and improving the luminous efficiency and lifespan. #imgabs0#I;#imgabs1#II.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of OLED, and specifically comprises an organic compound having multiple heteroatoms and an organic electroluminescent device comprising the same. Background Art

[0002] In order to improve the brightness and efficiency of organic electroluminescent devices, the use of stacked OLED devices with multiple OLED light-emitting units in series has become a new trend in future research. Compared with a single OLED light-emitting unit, stacked OLED devices usually have higher current efficiency, brightness and lifespan.

[0003] In a stacked OLED device, two independent light-emitting units are connected in series through a charge generation layer (CGL). The charge generation layer is usually constructed in the form of a pn structure. The stability of the charge generation layer has a great influence on the device life and driving voltage. In the traditional n-type charge generation layer, nCGL materials are often doped with metals with low work functions (such as Li, Mg, Yb, etc.) to form a complex. However, due to the poor thermal stability and low electron transfer rate of the currently developed nCGL materials, the stability of the device becomes worse after being doped with metals, which restricts the commercialization process of stacked devices to a certain extent.

[0004] The current mainstream nCGL materials are mainly based on nitrogen heteroaromatic ring structures such as pyridine, pyrimidine, and phenanthroline. Such structures can no longer meet the growing technical requirements in terms of electron transport capacity. In addition, some of the currently disclosed nCGL materials containing phosphine and phenanthroline also have problems such as unstable coordination with metals and poor thermal stability of the materials themselves. Summary of the invention

[0005] In view of the above problems existing in the prior art, the present invention provides an organic compound having multiple heteroatoms and an organic electroluminescent device comprising the same.

[0006] To achieve the above objectives, the technical solutions adopted by the present invention include:

[0007] The first aspect of the present invention provides an organic compound having multiple heteroatoms, the general structural formula of the organic compound is shown in Formula I:

[0008] I; II;

[0009] Wherein, R1-R4 each independently represents hydrogen, deuterium, a substituted or unsubstituted alkyl group having carbon atoms of C1-C30, a substituted or unsubstituted aryl group having carbon atoms of C6-C60, a substituted or unsubstituted condensed aromatic group having carbon atoms of C6-C60, or any one of the groups shown in formula II, and at least two of R1-R4 represent the groups shown in formula II;

[0010] L1-L4 each independently represent a single bond, a substituted or unsubstituted aryl group having C6-C60 carbon atoms, a substituted or unsubstituted heteroaryl group having C5-C60 carbon atoms, a substituted or unsubstituted condensed ring aryl group having C6-C60 carbon atoms, or a substituted or unsubstituted heterocondensed ring aryl group having C5-C60 carbon atoms.

[0011] Furthermore, R1 and R2 each independently represent a group shown in formula II, and R3 and R4 do not represent a group shown in formula II.

[0012] Furthermore, R3 and R4 each independently represent a group shown in formula II, and R1 and R2 do not represent a group shown in formula II.

[0013] Further, said L1-L4 each independently represents a single bond, , , , , Any one of .

[0014] Furthermore, L1-L4 each independently represents one of the following structures:

[0015] , , , , , , , .

[0016] Furthermore, R1 and R2 represent the same group, R3 and R4 represent the same group, L1 and L2 represent the same group, and L3 and L4 represent the same group. That is, when the structure of Formula I is a symmetrical structure, it is better for reducing the maximum negative electrostatic potential (ESP) of the material, improving the stability of the material after being doped with metal, improving the electron transmission ability of the material, and improving the device voltage and device life.

[0017] Furthermore, the organic compound is selected from one of the following structures:

[0018] I-1, I-2, I-3, I-4.

[0019] Furthermore, the organic compound is selected from one of the following structures:

[0020] .

[0021] The second aspect of the present invention provides an organic electroluminescent device, comprising an anode, a first hole transport region, a first light-emitting layer, a first electron transport region, a charge generation region, a second hole transport region, a second light-emitting layer, a second electron transport region, a cathode, and a covering layer, which are sequentially arranged on a substrate; wherein the charge generation region includes one or more organic compounds as described above.

[0022] Furthermore, the charge generation region includes an n-type charge generation layer and a p-type charge generation layer, wherein the n-type charge generation layer includes one or more organic compounds as described above.

[0023] Beneficial effects of the present invention:

[0024] In the development of the nCGL material of the present invention, according to the Pauling rule, by using the structural combination of phosphine + phenanthroline in the nCGL material, using high electronegativity atoms such as nitrogen, oxygen, and phosphine, the maximum negative electrostatic potential (ESP) of the nCGL material is significantly reduced. When used in combination with n-doped metals with low electronegativity, the stability of the device film layer of the nCGL material after metal doping is improved, the electron transmission ability of the nCGL material is improved, the device voltage and device life are improved, and the increase in electronegativity can reduce the electron injection barrier, improve the electron mobility of the nCGL layer, and thus reduce the driving voltage. Further, when the nCGL material presents an axially symmetrical structural feature, it is more advantageous to improve the electron transmission ability of the material and improve the device voltage and device life. In addition, in the structural design, attention should be paid to adding a spacer (i.e., L1-L4) to multiple electron-withdrawing groups to avoid the reduction of material stability caused by the concentration of electron-withdrawing groups. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a schematic structural diagram of the organic electroluminescent device of the present invention. DETAILED DESCRIPTION

[0026] In order to more clearly understand the content of the present invention, it will be described in detail with reference to the drawings and embodiments.

[0027] The organic compound of the present invention is suitable for use in light-emitting elements, display panels and electronic devices, and is particularly suitable for use in organic electroluminescent devices. The electronic device of the present invention is a device comprising a layer of at least one organic compound, and the device may also comprise an inorganic material or a layer formed entirely of an inorganic material. The electronic device is preferably an organic electroluminescent device (OLED). The schematic structural diagram of an exemplary organic electroluminescent device is shown in FIG. Figure 1 shown.

[0028] Experimental Section

[0029] In order to understand the content of the present invention more clearly, the luminescent characteristics of the organic compound, the preparation method of the organic compound and the device will be explained in detail in conjunction with the examples. Various chemical reactions can be applied to the synthetic method of the compound of one embodiment of the present invention. However, it should be noted that the synthetic method of the compound of one embodiment of the present invention is not limited to the synthetic method described below. Unless otherwise indicated, the subsequent synthesis is carried out in anhydrous solvent under a protective gas atmosphere. Solvents and reagents can be purchased from conventional reagent suppliers.

[0030] Synthesis Example

[0031] In the structure described in this patent, if the substituents on both sides of phenanthroline are the same, the target product can be obtained in one step by using Suzuki coupling. The chemical reaction equation is as follows:

[0032]

[0033] If the substituents on both sides of phenanthroline are different, the target product can be obtained by two-step Suzuki coupling. The chemical reaction equation is as follows:

[0034]

[0035] Synthesis Example 1

[0036]

[0037] A1 (8.0 g, 20 mmol), B1 (16.2 g, 40 mmol) and potassium carbonate (8.2 g, 60 mmol) were added to a mixed solution of 300 ml toluene: water = 4:1 (V / V), and then tetrakistriphenylphosphine palladium (2.3 g, 2 mmol) was introduced under nitrogen protection, and then the reaction system was heated to 110 ° C, refluxed and maintained for 8 hours, cooled to room temperature, quenched with water and separated, the organic phase was dried with anhydrous sodium sulfate, the solvent was removed by rotation, and the crude product was separated and purified by petroleum ether: dichloromethane = 1:1 (V / V) column. Finally, the product C1 was obtained: 13.7 g, yield: 77%, MS (m / z) (M+): 886.

[0038] Synthesis Example 2

[0039]

[0040] Using the same method as in Synthesis Example 1, A2 (5 g, 20 mmol) and B2 (16.2 g, 40 mmol) were used to replace A1 and B1, and finally the product C2 was obtained: 10.5 g, yield: 71%, MS (m / z) (M+): 734.

[0041] Synthesis Example 3

[0042]

[0043] The same method as in Synthesis Example 1 was used to replace A1 and B1 with A3 (8 g, 20 mmol) and B3 (18.2 g, 40 mmol), and finally the product C3 was obtained: 15.7 g, yield: 80%, MS (m / z) (M+): 986.

[0044] Synthesis Example 4

[0045]

[0046] A4-1 (8.0 g, 20 mmol), B4-1 (8.1 g, 20 mmol) and potassium carbonate (4.1 g, 30 mmol) were added to a mixed solution of 300 ml toluene: water = 4:1 (V / V), and then tetrakistriphenylphosphine palladium (1.2 g, 1 mmol) was introduced under nitrogen protection, and then the reaction system was heated to 110 ° C, refluxed and maintained for 8 hours, cooled to room temperature, quenched with water and separated, the organic phase was dried with anhydrous sodium sulfate, the solvent was removed by rotation, and the crude product was separated and purified by petroleum ether: dichloromethane = 2:1 (V / V) column. Finally, the product A4-2 was obtained: 7.4 g, yield: 57%, MS (m / z) (M+): 644.

[0047] A4-2 (7.4 g, 11.5 mmol), B4-2 (5.5 g, 11.5 mmol) and potassium carbonate (4.1 g, 30 mmol) were added to a 300 ml mixed solution of toluene: water = 4:1 (V / V), and then tetrakistriphenylphosphine palladium (1.2 g, 1 mmol) was introduced under nitrogen protection, and then the reaction system was heated to 110 ° C, refluxed and maintained for 8 hours, cooled to room temperature, quenched with water and separated, the organic phase was dried with anhydrous sodium sulfate, the solvent was removed by rotation, and the crude product was separated and purified by petroleum ether: dichloromethane = 1:1 (V / V) column. Finally, the product C4 was obtained: 6.2 g, yield: 56%, MS (m / z) (M+): 962.

[0048] Synthesis Example 5

[0049]

[0050] The same method as in Synthesis Example 1 was used to replace A1 and B1 with A5 (5 g, 20 mmol) and B5 (19.2 g, 40 mmol), and finally the product C5 was obtained: 13.6 g, yield: 77%, MS (m / z) (M+): 886.

[0051] Synthesis Example 6

[0052]

[0053] The same method as in Synthesis Example 1 was used to replace A1 and B1 with A6 (5 g, 20 mmol) and B6 (16.2 g, 40 mmol), and finally the product C6 was obtained: 11.5 g, yield: 78%, MS (m / z) (M+): 734.

[0054] Synthesis Example 7

[0055]

[0056] A7-1 (5.5 g, 20 mmol), B7-1 (8.1 g, 20 mmol) and potassium carbonate (4.1 g, 30 mmol) were added to a mixed solution of 300 ml toluene: water = 4:1 (V / V), and then tetrakistriphenylphosphine palladium (1.2 g, 1 mmol) was introduced under nitrogen protection, and then the reaction system was heated to 110 ° C, refluxed and maintained for 8 hours, cooled to room temperature, quenched with water and separated, the organic phase was dried with anhydrous sodium sulfate, the solvent was removed by rotation, and the crude product was separated and purified by petroleum ether: dichloromethane = 2:1 (V / V) column. Finally, the product A7-2 was obtained: 7.1 g, yield: 73%, MS (m / z) (M+): 486.

[0057] A7-2 (7.1 g, 14.6 mmol), B7-2 (5.9 g, 14.6 mmol) and potassium carbonate (4.1 g, 30 mmol) were added to a mixed solution of 300 ml toluene: water = 4:1 (V / V), and then tetrakistriphenylphosphine palladium (1.2 g, 1 mmol) was introduced under nitrogen protection, and then the reaction system was heated to 110 ° C, refluxed and maintained for 8 hours, cooled to room temperature, quenched with water and separated, the organic phase was dried with anhydrous sodium sulfate, the solvent was removed by rotation, and the crude product was separated and purified by petroleum ether: dichloromethane = 1:1 (V / V) column. Finally, the product C7 was obtained: 8.1 g, yield: 73%, MS (m / z) (M+): 762.

[0058] Synthesis Example 8

[0059]

[0060] The same method as in Synthesis Example 1 was used to replace A1 and B1 with A8 (8 g, 20 mmol) and B8 (9.6 g, 40 mmol), and finally the product C8 was obtained: 16.3 g, yield: 79%, MS (m / z) (M+): 1038.

[0061] Synthesis Example 9

[0062]

[0063] Using the same method as in Synthesis Example 1, A9 (5 g, 20 mmol) and B9 (11.1 g, 40 mmol) were used to replace A1 and B1, and finally the product C9 was obtained: 16.2 g, yield: 78%, MS (m / z) (M+): 1038.

[0064] Synthesis Example 10

[0065]

[0066] The same method as in Synthesis Example 1 was used to replace A1 and B1 with A10 (10.3 g, 20 mmol) and B10 (9.1 g, 40 mmol), and finally the product C10 was obtained: 16.4 g, yield: 75%, MS (m / z) (M+): 1098.

[0067] Comparative Examples 1-4

[0068] The following provides compounds D1-D4 that were tested during the research process, and their specific structural formulas are as follows:

[0069]

[0070] Material performance evaluation

[0071] Maximum negative electrostatic potential (ESP): When there are multiple electronegative electron-withdrawing substituents in the material structure, the overall electronegativity of the molecular structure will increase, thereby improving the material's electron transport ability and its ability to coordinate with metal-doped materials. The electronegativity of a molecule can be evaluated by the maximum negative electrostatic potential (ESP). The larger the absolute value of ESP, the greater the electronegativity of the molecule and the better its nucleophilicity. ORCA was used to evaluate the ESP of the compounds in the synthetic examples and comparative examples under B3LYP / 6-31G** conditions.

[0072] Dissociation energy (BDE): The service life of OLED is determined by the stability of the chemical bond energy of the material. The higher the chemical bond energy, the more likely the material will continue to decompose when the material is heated and evaporated and when the OLED is powered on. The strength of the chemical bond can be measured by the bond dissociation energy (BDE). The smaller the bond dissociation energy, the weaker the bond and the more unstable the compound. Using Orca software, the B3LYP / 6-31G(d) method is used to calculate the dissociation energy of each chemical bond. The higher the dissociation energy, the more stable the chemical bond in the structure. The stability of the material is evaluated by comparing the minimum dissociation energy of chemical bonds between different structures.

[0073] The material performance evaluation results are shown in Table 1.

[0074] Table 1

[0075]

[0076] From the calculation results, it can be seen that the maximum negative electrostatic potential (ESP) and dissociation energy (BDE) of the overall molecule of the compound in the synthesis example are significantly better than those of the compound in the comparative example by using multiple electronegative groups, indicating that the compound in the synthesis example has greater electronegativity, better nucleophilicity, and its chemical bond is more stable.

[0077] The reason for the above results is that, compared with Comparative Examples 2 and 3, the compounds provided by the present invention significantly increase the absolute value of ESP by connecting a phosphine oxygen substituent with greater electronegativity to phenanthroline, especially compared with Comparative Example 2, because the oxygen atom is in the second period, its electronegativity is significantly greater than that of the sulfur atom in the third period, so the absolute value of ESP increases. Compared with Comparative Example 1, the compounds of the present invention can avoid the reduction of BDE caused by excessive concentration of electron-withdrawing groups by using a spacer, thereby improving the stability of the material. Compared with Comparative Example 4, the absolute value of ESP can be increased by using multiple phosphine oxygen substituents.

[0078] Fabrication and characterization of OLEDs

[0079] Device Embodiment

[0080] The organic electroluminescent device provided by the present invention comprises an anode, a first hole transport region, a first light-emitting layer, a first electron transport region, a charge generation region, a second hole transport region, a second light-emitting layer, a second electron transport region, a cathode, and a covering layer which are sequentially arranged on a substrate;

[0081] Further, the first hole transport region includes a hole injection layer, a first hole transport layer and a first electron blocking layer; the first electron transport region includes a first hole blocking layer and a first electron transport layer; the charge generation region includes an n-type charge generation layer and a p-type charge generation layer; the second hole transport region includes a second hole transport layer and a second electron blocking layer; the second electron transport region includes a second hole blocking layer, a second electron transport layer and an electron injection layer.

[0082] Furthermore, the light-emitting layer is composed of a main material and a doping material, and the main material of the light-emitting layer can be composed of one molecular material or multiple molecular materials.

[0083] The deuterated organic compound of the present invention can be used in one or more layers of the above-mentioned organic electroluminescent device, preferably used as the n-type charge generation layer material of the device.

[0084] The anode in the embodiment adopts anode materials commonly used in the art, such as ITO, Ag or their multilayer structures. The hole injection layer adopts hole injection materials commonly used in the art, and F4TCNQ, HATCN, NDP-9, etc. are added for doping. The hole transport layer adopts hole transport materials commonly used in the art. The light-emitting layer adopts light-emitting materials and doping materials commonly used in the art, for example, it can be composed of a main material and a doping material. The electron transport layer adopts electron transport materials commonly used in the art. The electron injection layer adopts electron injection materials commonly used in the art, such as Liq, LiF, Yb, etc. The n-type charge generation layer material adopts the deuterated organic compound provided by the present invention. The cathode adopts materials commonly used in the art, such as metal Al, Ag or metal mixtures (Ag-doped Mg, Ag-doped Ca, etc.).

[0085] The electrode preparation method and the deposition method of each functional layer in this embodiment are conventional methods in the art, such as vacuum thermal evaporation or inkjet printing, etc., which will not be described in detail here. Only some process details and test methods in the preparation process are supplemented as follows:

[0086] Device Example 1

[0087] The substrates used in the present invention were subjected to the following operations: the ITO substrate was patterned so that its luminous area had a size of 3 mm×3 mm, and then water / isopropanol ultrasound, UV / ozone irradiation, and then dried at 100°C. After that, the ITO substrate was mounted on a substrate holder of a vacuum deposition device and the pressure was adjusted so that the vacuum rate became 1×10 -7 torr.

[0088] Subsequently, the following operations were performed: first, on the ITO layer (anode) formed on the substrate, a compound HTL-1 and a compound p-dopant-1 (the mass ratio of HTL-1 to p-dopant-1 was 97:3) were vacuum deposited at a thickness of 10 nm to form a hole injection layer; secondly, on the hole injection layer, a compound HTL-1 was vacuum deposited at a thickness of 20 nm to form a first hole transport layer; secondly, on the first hole transport layer, a compound EB-1 was vacuum deposited at a thickness of 5 nm to form a first electron blocking layer; and thirdly, on the first electron blocking layer, a mixture of a compound BH-1 and a compound BD-1 was vacuum deposited at a thickness of 20 nm to form a first The first light-emitting layer is a luminescent layer, wherein BH-1 is used as a host and BD-1 is used as a dopant, and the mass ratio of the host to the dopant is 98:2; then, on the first light-emitting layer, the compound HB-1 is vacuum deposited with a thickness of 5 nm to form a first hole blocking layer; then, on the first hole blocking layer, the compound ETL-1 and the compound LiQ (the mass ratio of ETL-1 to LiQ is 1:1) are vacuum deposited with a thickness of 15 nm to form a first electron transport layer; then, on the first electron transport layer, the compound C1 and Yb (the mass ratio of C1 to Yb is 98:2) are vacuum deposited with a thickness of 15 nm to form an n-type charge generation layer, and the compound HTL-1 and Compound p-dopant-1 (the mass ratio of HTL-1 to p-dopant-1 is 97:3) is used to form a p-type charge generation layer, and then on the hole generation layer, compound HTL-1 is vacuum deposited with a thickness of 20 nm to form a second hole transport layer, and then on the second hole transport layer, compound EB-1 is vacuum deposited with a thickness of 5 nm to form a second electron blocking layer, and then on the second electron blocking layer, a mixture of compound BH-1 and compound BD-1 is vacuum deposited with a thickness of 20 nm to form a second light-emitting layer, wherein BH-1 is used as a host and BD-1 is used as a dopant, and the mass ratio of the host to the dopant is 98:2; then on the second On the second light-emitting layer, the compound HB-1 was vacuum deposited with a thickness of 5 nm to form a second hole blocking layer; then on the above-mentioned second hole blocking layer, the compound ETL-1 and the compound LiQ (the mass ratio of ETL-1 to LiQ is 1:1) were vacuum deposited with a thickness of 15 nm to form a second electron transport layer; then on the above-mentioned second electron transport layer, Yb was deposited with a thickness of 1 nm to form an electron injection layer, and then on the above-mentioned electron injection layer, Mg and Ag (the mass ratio of Mg to Ag is 1:9) were deposited with a thickness of 15 nm to form a cathode, and then on the above-mentioned cathode, the compound CPL-1 was deposited with a thickness of 50 nm to form a covering layer, and a stacked organic electroluminescent device was prepared.

[0089] In addition to the materials used in the present invention, the molecular structures of the remaining materials in each layer of the device are as follows:

[0090]

[0091] Device Examples 2-10

[0092] The above method was used to prepare the compounds in the synthesis examples into organic electroluminescent devices, wherein C2 to C10 were used to replace C1 to prepare organic electroluminescent device examples 2-10.

[0093] Device Comparison Examples 1-4

[0094] The above method was used to prepare the compounds in the comparative examples into organic electroluminescent devices, wherein D1-D4 were used to replace C1 to prepare organic electroluminescent device comparative examples 1-4.

[0095] The OLED devices described above were tested by standard methods. For this purpose, at J = 10 mA / cm 2 The driving voltage, brightness, electroluminescent current efficiency (measured in cd / A) and external quantum efficiency (EQE, measured in percentage) of the organic electroluminescent device are determined at a current density of 200 mA / cm2, which is calculated from the current / voltage / luminescent density characteristic line (IVL characteristic line) showing Lambertian emission characteristics as a function of luminous density. The lifetime LT is defined as the time after which the brightness drops from the initial luminous brightness L0 to a specific proportion L1 when operating at a constant current J; J = 20 mA / cm2 2 The expression L1 = 90% means that at 20 mA / cm 2 When working under LT, the luminance drops to 90% of its initial value L0 after time LT. Similarly, J = 20 mA / cm 2 , L1 = 95% means at 20mA / cm 2 When working under LT, the luminous brightness drops to 95% of its initial value L0 after time LT.

[0096] The data of various OLED devices are summarized in Table 2. Various parameters of the device examples and the device comparative examples are compared to show the performance data of various OLED devices.

[0097] The test instruments and methods for testing the performance of the OLED devices in the above embodiments and comparative examples are as follows:

[0098] Quantum efficiency CE (cd / A) and color coordinates (CIEy) were tested using a spectrum scanner PhotoResearch PR-635;

[0099] Current density and lighting voltage: tested using a digital source meter Keithley 2400;

[0100] Blue index is obtained by dividing the quantum efficiency CE (cd / A) by the color coordinate (CIEy);

[0101] Life test: Use LT-96ch life test device.

[0102] Table 2 Device performance test results

[0103]

[0104] From the device results, it can be seen that through material structure design, phosphine oxygen and phenanthroline structures are introduced into the structure to enhance the introduction of highly electronegative atoms such as nitrogen, oxygen, and phosphine, and increase the maximum negative electrostatic potential of the molecule, which is conducive to effectively reducing the driving voltage of the prepared organic electroluminescent device and improving the luminous efficiency. At the same time, by improving the dissociation energy BDE, the life of the organic electroluminescent device can be improved.

[0105] Compared with Comparative Example 1, the compound of the present invention improves the material stability by adding a spacer, and the device life is significantly increased. At the same time, compared with Comparative Examples 2, 3, and 4, due to the increase in ESP and the improvement in electron transmission capacity, the driving voltage of the device is significantly improved. Due to the increase in the overall electron transmission capacity of the device, the carrier balance of the device is improved, and the device embodiment using the material of the present invention also has certain advantages in efficiency and life.

[0106] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. An organic compound having multiple heteroatoms, characterized in that: The general structural formula of the organic compound is shown in Formula I: AND; II; Said R1 and R2 each independently represent a group shown in formula II, and R3 and R4 do not represent a group shown in formula II; R3 and R4 represent any one of hydrogen, deuterium, an alkyl group having carbon atoms of C1-C30, and an aryl group having carbon atoms of C6-C60; L1-L2 each independently represents an aryl group having a carbon number of C6-C60, , , Any of the following; L3-L4 each independently represents a single bond, an aryl group having carbon atoms of C6-C60, , , Any of the following; The R1 and R2 represent the same group, the R3 and R4 represent the same group, the L1 and L2 represent the same group, and the L3 and L4 represent the same group.

2. The organic compound according to claim 1, characterized in that The L1-L2 each independently represents , , , , Any of the following; The L3-L4 each independently represents a single bond, , , , , Any one of .

3. The organic compound according to claim 1, characterized in that The L1-L4 each independently represents one of the structures shown below: 、 、 、 、 、 、 、 。 4. The organic compound according to claim 1, characterized in that The organic compound is selected from one of the following structures: I-3、 I-4。 5. An organic compound having multiple heteroatoms, characterized in that: The organic compound is selected from one of the following structures: 。 6. An organic compound having multiple heteroatoms, characterized in that: The general structural formula of the organic compound is shown below: I-1、 I-2; II; Wherein, R3 and R4 each independently represent a group represented by formula II; The L3-L4 each independently represents one of the structures shown below: 、 、 、 、 、 、 、 ; The L3 and L4 represent the same group.

7. The organic compound according to claim 6, characterized in that The organic compound is selected from one of the following structures: 。 8. An organic electroluminescent device, characterized in that: It includes an anode, a first hole transport region, a first light-emitting layer, a first electron transport region, a charge generation region, a second hole transport region, a second light-emitting layer, a second electron transport region, a cathode, and a covering layer, which are sequentially arranged on a substrate; wherein the charge generation region includes one or more organic compounds as described in any one of claims 1 to 7.

9. The organic electroluminescent device according to claim 8, characterized in that: The charge generation region comprises an n-type charge generation layer and a p-type charge generation layer, wherein the n-type charge generation layer comprises one or more organic compounds according to any one of claims 1 to 7.